The lexical form of the Odia Language prevalent on social media - Rudranarayan Mohapatra, Subhasmita Nayak (International Journal of Advanced Science and Technology, 2020)
Today, the whole world is treated as a family through the development of new communication technologies. Nowadays, the Internet has become an important means of communication and is become an irreplaceable choice for Internet users. And passing the messages to each other quickly and effectively through internet in any of the language is inevitable for every Netizen. This new kind of trend in language and its communication is called as “Net-speak”. The Net-Speaks is randomly affecting every language of the world including Odia, an east-coast language of India. In this paper we are trying to catered how Odia lexical writing and speaking pattern quickly deviating from its traditional or standard pattern. Therefore, this study attempts to investigate how social media influences Odia language representation style and the changing nature of Odia lexical writing. Keywords: Net-Speak, Social Media, Odia Language, Lexicon, Cyber Language